Radiative thermal analysis for four types of hybrid nanoparticles subject to non-uniform heat source: Keller box numerical approach - Chu, Yu-Ming; Khan, M. Ijaz; Abbas, Tasawar; Sidi, Maawiya Ould; Alharbi, Khalid Abdulkhaliq M; Alqsair, Umar F.; Khan, Sami Ullah; Khan, M. Riaz; Malik, M.Y. (Case studies in thermal engineering, 2022)
The advancement in the thermal engineering presented the idea of nanomaterials with stable thermal consequences and performances. The importance of hybrid nanomaterials attributes importance in solar energy production, electronics devices, heating systems, mechanical processes etc. The hybrid model is classified as a distinct thermal phenomenon with different tiny particles. The thermal evaluation of hybrid nanofluid containing four types of nanoparticles subject to the non-uniform heat source/sink and inclined magnetic field for two-dimensional unsteady flow due to permeable stretched surface has been numerically investigated. Four different types of nanoparticles, copper, titanium dioxide, silver and aluminum oxide have been considered with water base fluid. With the help of similarity transformation, we convert the governing partial differential equation into the ordinary differential equation. To solve these similarity equations a numerical technique known as Keller box method is used. The results are shown graphically and in tabular form. For special cases, comparison of numerical results to the previous results is presented with excellent agreement. The physical onset of parameters due to fluctuated heat transfer rate, wall shear force and Nusselt number is observed. It is observed that change in magnetic field inclination angle declines the velocity profile. The temperature profile can be effectively controlled with interaction of titanium oxide nanoparticles. The presence of heat source enhanced the nanoparticles temperature more effectively.